2022
DOI: 10.1039/d2nr03172h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning ceria catalysts in aqueous media at the nanoscale: how do surface charge and surface defects determine peroxidase- and haloperoxidase-like reactivity

Abstract: Designing the shape and size of catalyst particles, and their interfacial charge, at the nanometer scale can radically change their performance. We demonstrate this with ceria nanoparticles. In aqueous media,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…The surface area increases with synthesis time, whilst the Ce 3+ /Ce 4+ ratio scales inversely with decreasing ζ -potential (because Ce 4+ is reduced to Ce 3+ with time during the reaction). 41…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The surface area increases with synthesis time, whilst the Ce 3+ /Ce 4+ ratio scales inversely with decreasing ζ -potential (because Ce 4+ is reduced to Ce 3+ with time during the reaction). 41…”
Section: Resultsmentioning
confidence: 99%
“…The surface area increases with synthesis time, whilst the Ce 3+ /Ce 4+ ratio scales inversely with decreasing ζ-potential (because Ce 4+ is reduced to Ce 3+ with time during the reaction). 41 ζ-Potential measurements were carried out to evaluate the effect of reaction time on the surface potential and to obtain information about the stability of the colloidal system and its catalytic activity. Interactions of substrates with the catalyst surface may differ due to electrostatic attraction or repulsion.…”
Section: Surface Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently shown that the HPO-like activity is proportional to the ζ-potential of CeO 2 surfaces as it promotes the adsorption of negatively charged Br − . 38 Although a good correlation can be seen for CeO 2 shapes here (Figure S25), this does not explain the selective oxidation of the added Br − by the monodentate peroxo species on Ce 7c(111) (or Ce 6c(110) ). DFT computations were thus employed to study the interplay between surface peroxo species and neutral Br atoms.…”
Section: Characterization and Catalytic Testing Of Ceomentioning
confidence: 99%